Modeling of the developed flexible skirt air-cushion track vehicle model - Hossain, Altab; Rahman, Mohammed Ataur; Mohiuddin, A. K. M.; Iqbal, A.K.M. P. (2008)
This research work describes the mathematical model development and analysis of the flexible skirt air-cushion track vehicle model for the collection and transportation operation of oil palm fresh fruit bunches (FFB) on swamp peat terrain in Malaysia. The main criterion of this research work is to produce an economical design which possesses low bearing capacity (7kN/m2) for the swamp peat terrain. The track mechanism is used as the driving system to overcome the motion resistance and the flexible skirt air cushion which is supported by the pressurized air is used to increase the floatation capacity of the vehicle. The design and analysis of the flexible skirt air-cushion track vehicle model have been done using Ds CATIA V5 version 16. Air-cushion is pressurized by using a compressor which is powered by a DC motor. The mathematical model and design parameter simulations of the flexible air-cushion track vehicle model for straight motion have been considered for this study.